Nonlinear profile order for three-dimensional hybrid radial acquisition applied to self-gated free-breathing cardiac cine MRI *Project supported by the National Natural Science Foundation of China (Grant Nos. 81501463, 61671026, 81571669, and 81671853), the Natural Science Foundation of Guangdong Province, China (Grant No. 2014A030310360), Guangdong Innovative Research Team Program of China (Grant No. 2011S013), the Basic Research Project of Shenzhen City, China (Grant Nos. JCYJ20140417113430639 and JCYJ20160429172357751), the High-level Oversea Talent Program of Shenzhen City, China (Grant No. KQJSCX20160301144248), and Beijing Center for Mathematics and Information Interdisciplinary Sciences of China. (January 2017) - Zhu 朱, Yanchun 艳春; Spincemaille, Pascal; Liu 刘, Jing 静; Li 李, Shuo 硕; Nguyen, Thanh D; Prince, Martin R; Xie 谢, Yaoqin 耀钦; Wang 王, Yi 乙
Abstract : This paper presents a nonlinear profile order scheme for three-dimensional (3D) hybrid radial acquisition applied to self-gated, free-breathing cardiac cine magnetic resonance imaging (MRI). In self-gated, free-breathing cardiac cine MRI, respiratory and cardiac motions are unpredictable during acquisition, especially for retrospective reconstruction. Therefore, the non-uniformity of the k -space distribution is an issue of great concern during retrospective self-gated reconstruction. A nonlinear profile order with varying azimuthal increments was provided and compared with the existing golden ratio-based profile order. Optimal parameter values for the nonlinear formula were chosen based on simulations. The two profile orders were compared in terms of the k -space distribution and phantom and human image results. An approximately uniform distribution was obtained based on the nonlinear profile order for persons with various heart rates and breathing patterns. The nonlinear profile order provides more stable profile distributions and fewer streaking artifacts in phantom images. In a comparison of human cardiac cine images, the nonlinear profile order provided results comparable to those provided by the golden ratio-based profile order, and the images were suitable for diagnosis. In conclusion, the nonlinear profile order scheme was demonstrated to be insensitive to various motion patterns and more useful for retrospective reconstruction.